Morphokinetic analysis of human embryo development and its relationship to the female age: a retrospective time-lapse imaging study - Akhter, N.; Shahab, M. (Cellular and Molecular Biology, 2017)
Time-lapse imaging technique has provided embryologists with a unique chance of studying the embryo morphokineticsto select the most viable embryos for implantation in the field of IVF (In vitro fertilization).The conventional method of morphological evaluations has proved that maternal age affects the human embryo quality. This retrospective study carried out at Islamabad Clinic Serving Infertile Couples, Islamabad, Pakistan mainly focuses on the effect of female age on human embryo morphokinetics. A total number of 200 patients undergoing ICSI treatment cycles at the clinic were selected for the study and divided into five age groups (< 26, 26-30, 31-35, 36-40, and > 40 years). Embryo culture was done at 37°C, 6% CO2 and 5% oxygen for 5-6 days. Ten time-points were selected for kinetic analysis. The number of retrieved, matured, fertilized and cleaved oocytes showed highly significant difference (Pâ‰¤ 0.0001) when compared among different age groups. There was no significant difference in average morphokinetic time-points among young versus old women.Whereas timely cleaved embryos showed significant difference in tPNa i.e. time for pronuclear appearance (Pâ‰¤ 0.001), t4 and t5 i.e. time for 4 and 5-cell cleavage (Pâ‰¤ 0.05)among different age groups. The clinical pregnancy rates showed a decline with increasing age. These results indicate the effect of female age on time-lapse embryo morphokinetic parameters. In future the addition of time-lapse analysis in routine IVF can help to improve the success rate by selecting the most viable embryos for uterine transfer.